Post-seismic earthquake deformation monitoring in Peninsular Malaysia using global positioning system - Jhonny, Jhonny (2010)
Sundaland, which covers Peninsular Malaysia, Sumatra, Java, Borneo, Thailand, Myanmar, Cambodia, Laos and Vietnam, has moved towards the east before the Aceh earthquake, but shortly after the earthquake, the motion of most of Sundaland was towards the west. The main objective of this study is to monitor the post-seismic motion of Peninsular Malaysia due to the previous earthquakes such as Aceh 2004, Nias 2005 and Bengkulu 2007. Seventy eight (78) Malaysia Real Time Kinematic Network (MyRTKnet) and thirty (30) Global Positioning System (GPS) stations worldwide were used in this study. The Bernese 5.0 software with double difference strategy was used to process all the data. The results show that the west-northwest part has the worse deformation in comparison to the other parts. Generally, from 2004 until 2005 Peninsular Malaysia moved towards west-southwest by 8.2 cm per year but in 2006, there was a slight change in the motion. From 2006 until 2008, the southern part has moved towards east-southeast by 0.23 cm per year and the northern part moved towards west-southwest by 5.9 cm per year. These motions have caused different displacements between both northern and southern parts, and may have triggered local faults movement. The other objective of this study is to identify whether the Raub-Bentong suture had any seismic activity. In 2007 until 2009, several tremors were recorded in Bukit Tinggi, Kuala Pilah, and Jerantut areas. These tremors are believed as indications of fault movement in Bukit Tinggi, Kuala Lumpur or Raub-Bentong. The determination of fault movement in this study was based on selected MyRTKnet baselines analysis. The technique is unable to identify the fault movement due to the fact that MyRTKnet stations are sparse and are far away from the fault lines. Therefore, it is necessary to carry out GPS field campaign along Bukit Tinggi and Kuala Lumpur faults in the future. Besides that, continuous post-seismic monitoring is needed to get a better picture of the seismic cycle in Peninsular Malaysia.